The News under Russia's Old Regime : the Development of a Mass-Circulation Press. - McReynolds, Louise (Princeton legacy library., 2014)
In this lively account of the rise of a commercial newspaper industry in imperial Russia, Louise McReynolds explores how the mass-circulation press created a forum for popular opinion advocating political change. From the Great Reforms of Tsar Alexander II in 1855 to the Bolsheviks' shut-down of the newspapers in 1917, she chronicles the exploits of publishers and editors, writers and readers. Arguing that this prosperous industry both expressed and shaped the development of ideas among new social groups, McReynolds provides insight into the growth in Russia of a fragile pluralism character.